Non-reassuring foetal status and neonatal irritability in the Japan Environment and Children's Study: A cohort study. Issue 1 (December 2018) - Morokuma, Seiichi; Michikawa, Takehiro; Kato, Kiyoko; Sanefuji, Masafumi; Shibata, Eiji; Tsuji, Mayumi; Senju, Ayako; Kawamoto, Toshihiro; Ohga, Shouichi; Kusuhara, Koichi
Abstract The aim of this study was to investigate whether non-reassuring foetal status (NRFS) affected an infant's temperament, or if the temperament formed prenatally resulted in an excessive heart rate reaction that was diagnosed as NRFS. We examined the correlation between NRFS and difficulty in holding a baby, and the amount of crying in the one month after birth, which was considered an indicator of the newborn's temperament. We divided the cases with NRFS into positive NRFS and false positive NRFS. NRFS was associated with bad mood, frequent crying for a long duration, and intense crying. After adjustment for other covariates, NRFS was associated with bad mood (odds ratio, OR = 1.15, 95% confidence interval, CI = 1.00–1.33), and intense crying (1.12, 1.02–1.24). In the multi-variable model, positive and false positive NRFS were not clearly associated with neonatal irritability. When stratified by parity, NRFS and false positive NRFS were likely to be positively associated with neonatal irritability in parous women. The clear association between NRFS and intense crying was observed in parous women (multi-variable adjusted OR = 1.46, 95% CI = 1.16–1.83), but not in nulliparae (1.01, 0.91–1.12) (p for effect modification <0.01). Similarly, increased odds of intense crying associated with false positive NRFS were only found in parous women (multi-variable adjusted OR = 1.40, 95% CI = 1.09–1.81) (p for effect modification = 0.03). There was no association observed between positive NRFS and irritability; therefore, NRFS has no effect on an infant's temperament.